2018
DOI: 10.1177/0954406218797976
|View full text |Cite
|
Sign up to set email alerts
|

Fully coupled thermo-magneto-electro-elastic properties of unidirectional smart composites with a piezoelectric interphase

Abstract: In the present study, the effect of PZT-5A piezoelectric interphase on the effective thermo-magneto-electro-elastic properties of CoFe2O4 piezomagnetic matrix composites reinforced with carbon fibers is investigated. In this type of three-phase smart composite, the unidirectional fiber is coated with the piezoelectric shell. To this end, the fully coupled thermo-magneto-electro-elastic constitutive relations are developed for a unit cell-based micromechanical model in conjunction with a proper representative v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This decline in the piezoelectric and dielectric properties is due to the decrease in the number of charge carriers in the insulating polymer matrix [84]. As a solution for the above problems researchers have started to investigate three phase composites that consist of ferroelectric and conductive inclusions that are randomly distributed in an uniform polymer matrix [20,22,[106][107][108][109]. While many have demonstrated notable piezoelectric values [108,[110][111][112], processing technique, active filler surface morphology and size/shape inherently influence the electromechanical performance of the samples.…”
Section: Electrically Conductive Fillermentioning
confidence: 99%
“…This decline in the piezoelectric and dielectric properties is due to the decrease in the number of charge carriers in the insulating polymer matrix [84]. As a solution for the above problems researchers have started to investigate three phase composites that consist of ferroelectric and conductive inclusions that are randomly distributed in an uniform polymer matrix [20,22,[106][107][108][109]. While many have demonstrated notable piezoelectric values [108,[110][111][112], processing technique, active filler surface morphology and size/shape inherently influence the electromechanical performance of the samples.…”
Section: Electrically Conductive Fillermentioning
confidence: 99%
“…Kattimani [26] proposed an optimal control of vibration in MEE plates by employing active constrained layer damping (ACLD) treatment. The effects of piezoelectric interphase on the thermo-MEE characteristics of coated unidirectional smart composites were studied by Haghgoo et al [27,28]. Vinyas [29] demonstrated that combining CNTs and MEE materials, due to the multi-physical coupling, can strengthen the vibratory characteristics of structures.…”
Section: Introductionmentioning
confidence: 99%
“…Todays, functionally graded material (FGM) together with functionally graded intelligent materials such as functionally graded piezoelectric material (FGPM) and functionally graded magneto-electro-elastic (FGMEE) have ever-increasing usages in the various industries because of their excellent feature. [1][2][3][4][5] Also, magneto-electro-elastics as composites including both piezoelectric and magnetostrictive components exhibit better performance than single-phase smart material as a result of the magneto-electric interaction effect. 6 Consequently, as a new type of intelligent materials, FGMEEs are considered and employed as high performance sensors and actuators in smart structures.…”
Section: Introductionmentioning
confidence: 99%